Hume's epistemology and metaphysics : an introduction - Dicker, Georges, 1942- (Routledge, 1998)
Key features of the book include discussion of Kant's responses to Hume and consideration of more recent responses to Hume's philosophy, allowing the full significance of his thought for contemporary philosophy to emerge.